2020
DOI: 10.1177/0269216320929549
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and caregivers’ experiences of driving with chronic breathlessness before and after regular low-dose sustained-release morphine: A qualitative study

Abstract: Background: Chronic breathlessness is a disabling syndrome that profoundly impacts patients’ and caregivers’ lives. Driving is important for most people, including those with advanced disease. Regular, low-dose, sustained-release morphine safely reduces breathlessness, but little is known about its impact on driving. Aim: To understand patients’ and caregivers’ (1) perspectives and experiences of driving with chronic breathlessness; and (2) perceived impact of regular, low-dose, sustained-release morphine on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 55 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…In fear of the occurrence of respiratory depression or other adverse effects, physicians indicate to be hesitant to prescribe opioids to patients with advanced COPD. [92][93][94] Systematic reviews on the effects of opioids on chronic breathlessness showed no evidence for an effect of opioids on respiratory outcomes. [82][83][84] On the contrary, three case reports have described cases of serious respiratory depression after high doses of nebulized morphine, 95 immediate-release oral morphine 96 or transmucosal fentanyl.…”
Section: Safety and Adverse Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…In fear of the occurrence of respiratory depression or other adverse effects, physicians indicate to be hesitant to prescribe opioids to patients with advanced COPD. [92][93][94] Systematic reviews on the effects of opioids on chronic breathlessness showed no evidence for an effect of opioids on respiratory outcomes. [82][83][84] On the contrary, three case reports have described cases of serious respiratory depression after high doses of nebulized morphine, 95 immediate-release oral morphine 96 or transmucosal fentanyl.…”
Section: Safety and Adverse Effectsmentioning
confidence: 99%
“…91 For patients with COPD, driving is also essential to attend therapy or go to a doctor's appointment. 92,93 Due to possible adverse effects as dizziness, patients are advised against driving during therapy initiation or upward dose titration. Where high doses can impair driving, 94 patients receiving stable lowdose morphine and their caregivers don't experience impairment of driving skills of the patient.…”
Section: Willingness Of Patientsmentioning
confidence: 99%
See 3 more Smart Citations